Worldwide Emergence of Extensively Drug-resistant Tuberculosis - Shah, N. Sarita; Wright, Abigail; Bai, Gill-Han; Barrera, Lucia; Boulahbal, Fadila; Martín-Casabona, Nuria; Drobniewski, Francis; Gilpin, Chris; Havelková, Marta; Lepe, Rosario; Lumb, Richard; Metchock, Beverly; et al. (Emerging infectious diseases, 2007)
Mycobacterium tuberculosis strains that are resistant to an increasing number of second-line drugs used to treat multidrug-resistant tuberculosis (MDR TB) are becoming a threat to public health worldwide. We surveyed the Network of Supranational Reference Laboratories for M. tuberculosis isolates that were resistant to second-line anti-TB drugs during 2000-2004. We defined extensively drug-resistant TB (XDR TB) as MDR TB with further resistance to > or = 3 of the 6 classes of second-line drugs. Of 23 eligible laboratories, 14 (61%) contributed data on 17,690 isolates, which reflected drug susceptibility results from 48 countries. Of 3,520 (19.9%) MDR TB isolates, 347 (9.9%) met criteria for XDR TB. Further investigation of population-based trends and expanded efforts to prevent drug resistance and effectively treat patients with MDR TB are crucial for protection of public health and control of TB.